Amir wants to show that tan3θ = (3tanθ-tan^3θ)/(1-3tan^2θ). He says he should use the double angle formula for the tangent function to do this. Is he correct?
A. Yes he can write tan 3θ= tan 2(3/2 θ) and use the double angle formula
B. Yes he can write tan 3θ=(2θ+θ) and use the sum formula followed by the double angle formula
C. no. Because 3 is not a multiple of 2, he will have a 3/2 θ term that cannot be simplified
D. no. Because tan 2θ=(2tanθ)/(1-tan^2θ) there is no way to multiply the denominator by 3 to obtain 1-3tan^2θ